2014
DOI: 10.1039/c4cp02741h
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study on the full ALD process of silicon nitride thin film deposition via BDEAS or BTBAS and NH3

Abstract: A detailed reaction mechanism has been proposed for the full ALD cycle of Si3N4 deposition on the β-Si3N4(0001) surface using bis(diethylamino)silane (BDEAS) or bis(tertiarybutylamino)silane (BTBAS) as a Si precursor with NH3 acting as the nitrogen source. Potential energy landscapes were derived for all elementary steps in the proposed reaction network using a periodic slab surface model in the density functional approximation. Although the dissociative reactivity of BTBAS was slightly better than that of BDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Amorphous Si 3 N 4 thin fi lms are widely used as passivation layers, masking layers to prevent oxidation in underlying materials and as a fi nal protection layer due to their hardness and radiation resistance. [57][58][59] There is great interest in developing new ALD processes for SiC and elemental Si itself.…”
Section: Modeling the Ald Of Silicon-based Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amorphous Si 3 N 4 thin fi lms are widely used as passivation layers, masking layers to prevent oxidation in underlying materials and as a fi nal protection layer due to their hardness and radiation resistance. [57][58][59] There is great interest in developing new ALD processes for SiC and elemental Si itself.…”
Section: Modeling the Ald Of Silicon-based Materialsmentioning
confidence: 99%
“…[ 65 ] Although chlorosilanes (e.g., SiCl 4 , SiH 2 Cl 2 and Si 2 Cl 6 ) are currently used for ALD of silicon nitride with NH 3 or N 2 as nitrogen source, [57][58][59]66,67 ] a chlorine-free low-temperature CVD or, ideally, ALD process would be preferred for many applications. Finding alternative Si precursors, and optimizing existing families such as aminosilanes, is therefore the motivation for some of the theoretical work presented here and for ongoing research.…”
Section: Modeling the Ald Of Silicon-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later in 2004, Mui et al investigated SiN x ALD with SiH 4 and NH 3 using DFT calculations [126]. This pioneering work has revealed that the reactions have to overcome high activation barriers which is challenging for thermal ALD [127]. Recently, the collaboration between academia and industry has contributed to the surge of theoretical simulation studies of SiN x ALD [34,54,57,127,128,129].…”
Section: Current Research Progressmentioning
confidence: 99%
“…This pioneering work has revealed that the reactions have to overcome high activation barriers which is challenging for thermal ALD [127]. Recently, the collaboration between academia and industry has contributed to the surge of theoretical simulation studies of SiN x ALD [34,54,57,127,128,129]. Murray et al found that the orientation of hydrogen atoms connected to the hydroxyl (–OH) and amine (–NH 2 ) groups is quite different [128].…”
Section: Current Research Progressmentioning
confidence: 99%